Communicable Diseases Intelligence volume 14 issue 6 - 26 March 1990 - whole issue - No author listed (Communicable Diseases Intelligence, 1990)
Whole-issue pdf, comprising: Viruses, Chlamydias, Coxiellas, Rickettsias and Mycoplasmas Reporting Scheme Overseas briefs Original articles Pertussis - epidemic summer in Australia Tetracycline-resistant Gonorrhoea - Australia AIDS and HIV surveillance, Australia: 26 January 1990 AIDS update, international - 28 February 1990 AIDS in Romania Reporting Tables: Australia - Communicable Diseases Intelligence Period 1/3/90 to 14/3/90